THE ROLE OF FAMILY KNOWLEDGE IN THE INCIDENCE OF PULMONARY TUBERCULOSIS - Yustati, Eva (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Tuberculosis can be caused by the bacteria Mycobacterium tuberculosis, which attacks the lungs in 80% of cases. Socioeconomic conditions, age, gender, family knowledge and support, nutritional status, and smoking habits are some of the factors that influence pulmonary TB disease. This study aims to investigate the role of family support and knowledge in cases of pulmonary TB at the Lubuk Rukam Community Health Center, although smoking is not the main cause of the disease. Cross-sectional study of the population of TB patients who came to the polyclinic, consisting of 125 patients aged 23 to 50 years. Samples taken by chance from 80 samples in this study showed the results of univariate analysis of 12.5 percent, suffering from pulmonary TB who did not suffer 87.5 percent, 20.0 percent, and lack of knowledge 80.0 percent. There is family support of 25.0% and no family support of 75.0%. Bivariate analysis showed that the p value of 0.003 indicates that statistically there is a significant relationship between knowledge and the incidence of pulmonary tuberculosis. Meanwhile, family support had a p-value of 0.002. Statistically, there was a significant relationship between family support and the incidence of pulmonary TB. Conclusion: There was a significant relationship between understanding and family support and the incidence of pulmonary tuberculosis at the Lubuk Rukam Community Health Center.